Wordsworth's Soundings in the Aeneid. Issue 1 (April 2020) - Falconer, Rachel
Abstract : Wordsworth's translation of Virgil's Aeneid I–III has been largely neglected by Romanticists and classical reception scholars, in part because it is considered to be an unfinished, failed artistic project. Amongst a handful of scholars, Bruce Graver has convincingly demonstrated the originality of Wordsworth's Latin translation. This article goes further to suggest the artistic coherence of Wordsworth's translation of Virgil . Aeneid I–III trace the arc of Aeneas's fall and exile from Troy and discovery of a new home. In translating Aeneas's journey, Wordsworth enacts a quest for a new poetic voice, at a time when his creative powers as an English poet were at a low ebb. His engagement with Virgil's Latin can be compared to his encounters with Nature and the River Derwent in earlier poetry; in both cases, the poet plays host to an alienatingly other, divine maternal presence which eventually rejuvenates and confirms the poet's voice in English.